2012
DOI: 10.1021/nn3037368
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoclusters Exhibiting Protein-Activated Near-Infrared Fluorescence

Abstract: Composite nanoclusters with chemical, magnetic, and biofunctionality offer broad opportunities for targeted cellular imaging. A key challenge is to load a high degree of targeting, imaging, and therapeutic functionality onto stable metal-oxide nanoparticles. Here we report a route for producing magnetic nanoclusters (MNCs) with alkyne surface functionality that can be utilized as multimodal imaging probes. We form MNCs composed of magnetic Fe(3)O(4) nanoparticles and poly(acrylic acid-co-propargyl acrylate) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Moreover, PDT studies indicated the ICG-PA NPs with 780 nm radiation resulted in a statistically significant reduction in cell growth. Based on the results of these studies, Daniele et al further developed protein-activated ICG-magnetic nanoclusters [34]. The magnetic core could provide a MRI signal and ICG-BSA shell show a highly fluorescent imaging ability.…”
Section: Icg Conjugated Npsmentioning
confidence: 99%
“…Moreover, PDT studies indicated the ICG-PA NPs with 780 nm radiation resulted in a statistically significant reduction in cell growth. Based on the results of these studies, Daniele et al further developed protein-activated ICG-magnetic nanoclusters [34]. The magnetic core could provide a MRI signal and ICG-BSA shell show a highly fluorescent imaging ability.…”
Section: Icg Conjugated Npsmentioning
confidence: 99%
“…In addition, MNPs have been actively investigated as the next generation of targeted drug delivery and cancer theranostics [6,7]. In the case of MNPs, once they arrive in the bloodstream or tissue interstitial fluids, various proteins bind to MNPs surface by nano-bio interactions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be applied in the field of nanomedicine, where the more effective ways of targeted delivery are constantly researched. Nanomaghemite in complex offers both a presence as a contrast agent for MRI and/or as a photosensitizer for photodynamic therapy [35,36,37]. Moreover, a cationic lipoplex system may be helpful to improve the interactions of peptide-modified metal nanoparticles with bacterial membranes in peptide nanoparticles-based bacterial infection treatment [18], which represents a potential alternative of antibiotics, to which a larger resistance is still observed.…”
Section: Resultsmentioning
confidence: 99%